Teachers’ Views of Formation of Pupils Personal Educational Outcomes - Lubovsky, D.; Plesnevich, S.G. (Psihologiceskaâ nauka i obrazovanie (2007), 2017)
Teachers` perceptions of opportunities to provide students educational and personal outcomes in the circumstances of modern education were studied. The hypothesis was the assumption that teachers’ perceptions on the possibility of forming of schoolchildren’ personal educational results are related to their professionally important qualities. 72 teachers of one of Moscow gymnasium were examined with a questionnaire for identification ofteachers’ viewon possibility of forming of schoolchildren’ personal educational results and questionnaire of communicative and organizational tendencies KOS-1. The data showed that more than half of the teachers consider adequate professional competence for the formation of personal educational outcomes of students. There was a significant relation between the teachers’ viewof their commitment to the formation of personal educational schoolchildren’ results and the communicative and organizational aptitudes. Authors’ assumption is that professionally important qualities of a teacher are the internal basis for the formation of students’ personal educational outcomes.The importance of the activity approach in the education of future teachers to develop their professional aptitudes and abilities is stressed. Изучены представленияучителей о возможности сформировать у школьников личностные образовательные результаты в условиях современного образования. Гипотеза состояла в предположении, что представления учителей о формируемости личностных образовательных результатов учащихся связаны с их профессионально важными качествами. Были обследованы 72 учителя одной из гимназий г. Москвыс помощью анкеты по выявлению представлений о формируемости личностных образовательных результатов школьников и опросника коммуникативных и организаторских склонностей КОС-1. Установлено, что больше половины педагогов считают достаточными их профессиональные компетенции для формирования личностных образовательных результатов школьников.Выявлена значимая связь между представлениями педагогов об их готовности к формированию личностных образовательных результатов у школьников и коммуникативными и организаторскими склонностями этих педагогов. Высказано предположение о том, что профессиональноважные качества педагога выступают внутренней опорой в деятельности по формированию личностных результатов образования школьников. Подчеркнуто значение деятельностного подхода в образовании будущих учителей для формирования у них профессиональных склонностей и способностей.